2018
DOI: 10.1109/tns.2018.2820907
|View full text |Cite
|
Sign up to set email alerts
|

Total Ionizing Dose Effects on TiN/Ti/HfO2/TiN Resistive Random Access Memory Studied via Electrically Detected Magnetic Resonance

Abstract: We observe a gamma-irradiation induced change in electrically detected magnetic resonance (EDMR) in TiN/Ti/HfO2/TiN resistive random access memory (RRAM). EDMR measurements exclusively detect electrically active defects which are directly involved in the transport mechanisms within these devices. The EDMR response has an isotropic g-value of 2.001 ± 0.0003. The response increases dramatically with increased gamma-irradiation. We tentatively associate this EDMR response with spin dependent trap assisted tunneli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…We hypothesized that the radiation might affect the quality of the Ti/Al:HfO2 interface due to the radiation-induced defects in HfO2 films [2]. To validate this hypothesis, we measured larger devices having an area of 3025 µm 2 (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesized that the radiation might affect the quality of the Ti/Al:HfO2 interface due to the radiation-induced defects in HfO2 films [2]. To validate this hypothesis, we measured larger devices having an area of 3025 µm 2 (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…EMRISTOR offers excellent promises for space applications due to its facile architecture, lightweight design, and low power consumption [1]; moreover, several groups suggested that memristor devices, especially HfO2based, are intrinsically rad-hard [2]- [7]. However, these reports focus on the reliability studies of the devices, while the potential beyond erasable memory applications exploiting radiationinduced effects has not yet been explored.…”
Section: Introductionmentioning
confidence: 99%
“…The minor decrease in remnant polarization ( P r ) should be attributed to the screening effects of the trapped charger carriers induced by the increasing electron‐hole pairs under γ‐ray radiation environment. However, McCrory et al verified that defects of an O 2 − coupled to a hafnium ion induced by γ‐ray radiation are directly involved in the electronic transport of TiN/Ti/HfO 2 /TiN RRAM devices through electrically detected magnetic resonance (EDMR) . Ding has also discovered that oxygen vacancies caused by high dose rays are the dominant radiation‐induced defects in HfO 2 ‐based metal‐oxide‐semiconductor capacitors .…”
Section: Introductionmentioning
confidence: 99%
“…Recent irradiation experiments showed that HfO 2 ferroelectric thin films have a high radiation tolerance . Huang et al have found that Y‐doped HfO 2 ‐based (HfYO) thin films prepared by pulse laser deposition (PLD) have a much higher radiation‐hardened stability compared with other ferroelectric materials .…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work showed that irradiation-induced electrical characteristics degradation of MFIS structure of Pt/SrBi2Ta2O9/HfTaO/Si were found under the total dose of 10 Mrad (Si) [11]. D. J. McCrory et al verified the defects induced by γ-ray radiation to be an O2coupled to a hafnium ion of TiN/Ti/HfO2/TiN RRAM devices through electrically detected magnetic resonance (EDMR) [12]. It has verified that interface defects have been formed in the TiN/HfO2/Si MOS capacitor during irradiation, and the accumulation capacitance decreased with the increasing of irradiation dose [13].…”
Section: Introductionmentioning
confidence: 99%